Finding a Needle in a Haystack: The Effects of Searching and Learning on Pick-Worker Performance - Batt, Robert J.; Gallino, Santiago (Management Science, 2019)
The rise in online and multichannel retailing has pushed retailers to give increased attention to their order-fulfillment operations. We study “chaotic storage” fulfillment systems in which dissimilar items are stored together in a single location. This necessitates a searching task as part of the picking process, which has not been previously studied. We show that pick times increase by as much as 16% as the searching task becomes more difficult. However, the deleterious effect of searching decreases with pick-worker experience. Using simulation, we show that pick times can be improved by incorporating distance, bin density, and picker experience into pick assignments and pick routing. Through properly combining the details of the task and the workers, order-fulfillment productivity can be increased by approximately 5%. This paper was accepted by Vishal Gaur, operations management.